Pre‐feasibility study and design of a biogas recovery and transport system from the San José (Lambayeque) stabilization ponds towards a power generating station - Palacios M., Juan D. (2017)
The pre‐feasibility study and design of a biogas recovery and transport system for power generation was carried out. The purpose of this study was twofold: to reduce the emissions of greenhouse gases (GHG) produced by the anaerobic lagoons of the San José (Lambayeque) wastewater treatment plant; and to obtain a renewable energy source that could make the plant self‐sustaining. Initially, information on the current state of the system and on the plant operating conditions was collected. Then, after analyzing the data obtained and applying the guidelines of the Inter‐American Development Bank (IDB) for Clean Development Mechanism (CDM) projects, the amounts of GHG emitted in the environment was estimated to 33,885 t CO2e / year. Solutions to the problem were then proposed and, among them, a cover system was considered as the most appropriate. This allowed an estimation of the annual generation potential with the project and the reduction of emissions to 27,620.36 tC02 / year. With the above estimates, a preliminary design of the biogas plant was carried out. Finally, an economic evaluation was completed, giving a Net Present Value (NPV) and an Internal Rate of Return (IRR) that confirmed the pre‐feasibility of the project.